Investigation of the Solid Electrolyte Interphase Formation at Graphite Anodes in Lithium-Ion Batteries with Electrochemical Impedance Spectroscopy. (20th February 2017) - Steinhauer, Miriam; Risse, Sebastian; Wagner, Norbert; Friedrich, K. Andreas
Highlights: Electrochemical impedance spectra measured during the first and second lithiation. SEI formation was studied at elevated and lower temperatures. Arrhenius behavior calculated from the measured impedance spectra Abstract: To optimize lithium-ion batteries it is important to understand the formation of the solid electrolyte interphase (SEI) occurring at the graphitic anode during the first cycles. In this study we measured electrochemical impedance spectra at equidistant voltage intervals during first and second lithiation (charging process). The distribution of relaxation times (DRT) was calculated from the measured impedance spectra. Based on the DRT calculations an equivalent circuit was set up to evaluate the different impedance contributions. In addition to measurements at room temperature we also studied SEI behavior at elevated and lowered temperatures. Above 55 °C we monitored an unwanted thermally induced electrolyte decomposition. Below −10 °C an incomplete SEI formation was observed resulting in an increased impedance during the second lithiation. The activation energies of the different processes were calculated assuming Arrhenius behavior.